Assessment of operational space for long-pulse scenarios in ITER. (8th May 2015) - Polevoi, A.R.; Loarte, A.; Hayashi, N.; Kim, H.S.; Kim, S.H.; Koechl, F.; Kukushkin, A.S.; Leonov, V.M.; Yu. Medvedev, S.; Murakami, M.; Na, Y.S.; Pankin, A.Y.; et al.
Abstract: The operational space ( I p − n ) for long-pulse scenarios (Δ t burn ∼ 1000 s, Q ⩾ 5) of ITER has been assessed by 1.5D core transport modelling with pedestal parameters predicted by the EPED1 code by a set of transport codes under a joint activity carried out by the Integrated Operational Scenario ITPA group. The analyses include the majority of transport models (CDBM, GLF23, Bohm/gyroBohm (BgB), MMM7.1, MMM95, Weiland, scaling-based) presently used for interpretation of experiments and ITER predictions. The EPED1 code was modified to take into account boundary conditions predicted by SOLPS4 for ITER. In contrast to standard EPED1 assumptions, EPED1 with the SOLPS boundary conditions predicts no degradation of the pedestal pressure as density is reduced. Lowering the plasma density to n e ∼ (5–6) × 10 19 m −3 leads to an increased plasma temperature (similar pedestal pressure), which reduces the loop voltage and increases the duration of the burn phase to Δ t burn ∼ 1000 s with Q ⩾ 5 for I p ⩾ 13 MA at moderate normalized pressure ( β N ∼ 2). These ITER plasmas require the same level of additional heating power as the reference Q = 10 inductive scenario at 15 MA (33 MW NBI and 17–20 MW EC heating and current drive power). However, unlike the 'hybrid' scenarios considered previously, these H-mode plasmas do not require specially shaped q profiles nor improved confinement in the core for the transport models considered in this study. Thus, these medium density H-mode plasma scenarios with I p ⩾ 13 MA present an attractive alternative to hybrid scenarios to achieve ITER's long-pulse Q ⩾ 5 scenario and deserve further analysis and experimental demonstration in present tokamaks.